Pengembangan Media Pembelajaran Interaktif Berbasis Powerpoint Pada Mata Pelajaran IPAS Pada Siswa Kelas IV di SDN 1 Simbune Desa Simbune Kecamatan Tirawuta Kabupaten Koloka Timur - Anidi; Kusumawati, Intan; Syhafiq, Muh. Aqil (Academy of Education Journal, 2025)
Based on the results of interviews conducted by researchers with teachers in grade IV of SD Negeri Simbune, the variables of sources or learning media used by teachers in the learning process of science and technology cause students to be less interested in the subject matter taught. Environmental factors that can interfere with students' concentration in receiving learning materials. So that the response from students is less active and less enthusiastic in following the learning process with traditional methods. The objectives of this researcher are: 1) To develop interactive PowerPoint media that can be used in science learning, and 2) To describe the process of developing interactive PowerPoint media for science and science subjects in grade IV students at SDN 1 Simbune, Simbune Village, Tirawuta District, East Kolaka Regency. The results and conclusions in this research and development are: 1) The validity of PowerPoint-based interactive learning resources in the science science subject taught in grade IV of SD Negeri 1 Simbune with an average validity of 92.71%., and 2) Interactive learning media using PowerPoint for teaching science science to grade IV students of SD Simbune proved to be very practical, with students completing 89.79%.